Eating in Theory - Mol, Annemarie (Book collections on Project MUSE., 2021)
"Eating in Theory draws on snapshots of eating practices to shift a range of fundamental intellectual reflexes. The terms that shape current social science and humanities theorizing are marked by a hierarchical version of "the human" in which thinking is celebrated and eating is demoted to a mundane necessity. However much sense this may have made in the past, it works poorly in a time of ecological crisis. Drawing on ethnographic research into eating practices in the Netherlands, Eating in Theory re-thinks the core theory terms being, knowing, doing and relating. These are no longer external, distant, centered and companionable, but entangled, transformative, spread out and suspended between fostering and devouring"--